The Effect of Eight Weeks of Hydrotherapy on Quality Of Life of Elderly Women Residing in Jahrom, Iran: A Quasi-Experimental Study - Ehsan Rahmanian (Journal of Global Pharma Technology, 2017)
Introduction: Exercise is generally believed to be an effective method in preventing elderly disorders which delays elderly. Exercise programs and regular and continuous physical activities can increase the Quality Of Life (QOL) of elderly people, cause greater independence in daily tasks, and help a more favourable ageing process. Therefore, this research aimed to study the effect of 8 weeks of hydrotherapy on Quality Of Life of elderly women aged over 50 residing in Jerome, Iran. Method this is a quasi-experimental study by pretest-posttest design. A sample of 29 elderly women aged over 50 was selected using convenience sampling. Hydrotherapy was performed for 8 weeks (24 sessions). Quality Of Life was assessed at two stages (before and after hydrotherapy) by SF-36. Descriptive and inferential tests, paired t-test, and Kolmogorov- Smirnov Test were employed to analyze the data. Findings: The mean age of women was 51.04±9.63. No significant difference was found on the QOL before and after the intervention (P-Value>0.05). Paired t-test results showed that a significant difference was found on Role-Playing Limitation due to Emotional Reasons before and after the intervention (P-Value<0.05). A significant difference was also found on Physical Pain before and after the intervention (P-Value<0.05). No significant difference was found on QOL components (general health, physical functioning, role-playing limitations due to physical functioning, social functioning, vitality and mental health) before and after the intervention (P-Value>0.05). Conclusion: Although QOL declined after the intervention, the result was not statistically significant. Therefore, hydrotherapy was not effective in elderly women QOL. Keywords: Exercise, Hydrotherapy, Quality of Life, Elderly Women.